2022
DOI: 10.1186/s12913-022-07676-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of feedback in emergency ambulance services: a qualitative interview study

Abstract: Background Several international studies suggest that the feedback that emergency ambulance service (EMS) personnel receive on the care they have delivered lacks structure, relevance, credibility and routine implementation. Feedback in this context can relate to performance or patient outcomes, can come from a variety of sources and can be sought or imposed. Evidence from health services research and implementation science, suggests that feedback can change professional behavior, improve clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 54 publications
(70 reference statements)
1
34
0
Order By: Relevance
“…35 Our own qualitative work on feedback to emergency ambulance staff found CP-FIT to have good face validity when exploring causal mechanisms at an abstract level, for example, 'processing and reflection'. 12 To identify potential mechanisms at a more detailed level for this review, we used behaviour change theory, which aims to identify active ingredients of interventions seeking to change behaviour 36 and has previously been used to synthesise evidence from audit and feedback interventions. 37 38 CW identified potential causal mechanisms deductively using an established list of mechanisms of action from behaviour change theory, 36 with a researcher experienced in behaviour change theory coding (RL) verifying the assigned codes of a 20% (n=10) random sample.…”
Section: Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…35 Our own qualitative work on feedback to emergency ambulance staff found CP-FIT to have good face validity when exploring causal mechanisms at an abstract level, for example, 'processing and reflection'. 12 To identify potential mechanisms at a more detailed level for this review, we used behaviour change theory, which aims to identify active ingredients of interventions seeking to change behaviour 36 and has previously been used to synthesise evidence from audit and feedback interventions. 37 38 CW identified potential causal mechanisms deductively using an established list of mechanisms of action from behaviour change theory, 36 with a researcher experienced in behaviour change theory coding (RL) verifying the assigned codes of a 20% (n=10) random sample.…”
Section: Data Synthesismentioning
confidence: 99%
“…10-12 31 74 75 Concerns were that feedback was skewed towards the negative 10 75 and only triggered by highly traumatic incidents, 11 while EMS professionals desired routine, frequent and high-quality feedback. [10][11][12] One UK study suggested that EMS professionals desired 'pull'-type feedback, that is, initiated by individual clinicians, delivered electronically or involving staff mediators. 11 In addition to the feedback types identified in interventional studies (table 2), non-interventional studies also discussed patient experience feedback, which involved EMS…”
Section: Ems Professionals' Evaluation Of Feedback Provision (Non-int...mentioning
confidence: 99%
See 1 more Smart Citation
“… 54 This review highlighted a lack of clinician feedback, therefore ambulance clinician feedback systems should be implemented and maintained because previous research suggests clinical feedback may improve quality of care. 55 …”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should be encouraged to treat pain more readily to meet patient needs and expectations, making full use of nonpharmacological techniques when appropriate and to use analgesics even when perceived to be weaker, thus harnessing the psychosocial effect of analgesic administration 54 . This review highlighted a lack of clinician feedback, therefore ambulance clinician feedback systems should be implemented and maintained because previous research suggests clinical feedback may improve quality of care 55 …”
Section: Discussionmentioning
confidence: 99%